2017
DOI: 10.52964/amja.0644
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Readmissions – Independent Predictors of 30-day Readmissions derived from a 10 year Database

Abstract: Unplanned medical 30 day readmissions place a burden on the provision of acute hospital services and are increasingly used as quality indicators to assess quality of care in hospitals. Multivariable logistic regression of a 10 year database showed that four factors were most strongly associated with early readmission: Charlson comorbidity index >=1, respiratory disease as a principal diagnosis, liver disease and alcohol-related illness as an additional diagnosis, and the number of previous readmissions. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Indeed, older individuals are often characterized by clinical, functional, and social complexity that could affect both hospital LOS and readmission rates. In this regard, previous studies showed that many factors associated with a higher risk of rehospitalization, such as functional impairments, chronic diseases, and use of multiple medications [ 4 , 5 , 7 , 13 , 14 , 27 , 28 ], are highly prevalent in advanced age. Moreover, irrespective of the precipitating acute illness, hospital stay can affect per se older individuals’ cognitive and physical performance, making them more vulnerable to new health events and hospitalizations [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, older individuals are often characterized by clinical, functional, and social complexity that could affect both hospital LOS and readmission rates. In this regard, previous studies showed that many factors associated with a higher risk of rehospitalization, such as functional impairments, chronic diseases, and use of multiple medications [ 4 , 5 , 7 , 13 , 14 , 27 , 28 ], are highly prevalent in advanced age. Moreover, irrespective of the precipitating acute illness, hospital stay can affect per se older individuals’ cognitive and physical performance, making them more vulnerable to new health events and hospitalizations [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The burden of these events on the healthcare systems is even heavier considering that older age is associated with longer hospital stays [2] and more frequent 30-day readmissions [3,4]. Recent reports show that 30-day rehospitalization rates in the general population range between 10 and 20% [3][4][5][6][7], with nearly half of the readmissions deemed as potentially preventable [8,9].…”
Section: Introductionmentioning
confidence: 99%